1. The Canadian Experience in Mineral Resource Assessment - Sangster, D. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1983)
Summary The first Canada-wide, non-industry resource assessment was A.H. Lang's uranium metallogenic map, published in 1958. Since then approximately two dozen resource assessments of either the entire country or various parts of it have been produced by the federal and certain provincial geological surveys. Most research in resource assessment methods, however, has been carried out in the Geological Survey of Canada; some has been done within provincial geological surveys, but little or none has emerged from Canadian universities. Methods used in Canada during the 24-year span have ranged from statistically dominant and geologically subordinate to the reverse, and the resulting assessments have ranged from quantitative to qualitative. Of the various methods that have been proposed, developed and tested by far the most widely used is that employing conceptual models of separate and distinct types of deposits. The models are erected by mineral deposits geologists on the basis of experience, research and examination of many examples of each deposit-type. Essential and integral parts of each conceptual model are its regional geological parameters, and it is these parameters which are sought in resource evaluation studies using the conceptual model method. This method, as presently used in Canada, usually results in an arbitrary rating of selected areas in terms of their assessed potential to contain undiscovered deposits. Numerous examples of resource assessment using the conceptual model method recently have been published by both federal and provincial governments. These resource assessments are presented in such a manner that they can be used for government land use decisions as well as for initial phases of mineral exploration.